The Heart, Life, and Soul of Technology - Mojola, O. O. (Obafemi Awolowo University Press, 2013)
The ivory-tower ritual of delivering an inaugural lecture which I am now called upon to perform was of course transplanted into this country by the British. Within Britain itself, there was some semblance of this activity at the University of Oxford- at least as early as 1623 when, as the first Camden Professor of History, Digory Whear mounted the rostrum to deliver his oratio auspicalis in the Schola Grammaticae. By the time of Edward Thwaites (Regius Professor of Greek, also at Oxford) in 1708, the inaugural lecture had 'become somewhat _forrn alised, and the lecture has since come to be perceived by scholars as something of an intellectual feast prepared by the lecturer according to his own recipe. My recipe for this lecture, the first from the Department of Mechanical Engineering of this University, is a fairly brief e.~osition of some aspects of technology. The expose shall be lightly flavoured with summaries in the appropriate places of some of my contributions to knowledge and activities in the field for more than twenty years. I shall be di~ging into the past, tugging at the present, and (occasionally) crystal-gazing into the future. The thrust of my arguments shall be directed at some of those key elements which I consider to be the real foundations of technology. Hence my choice of a rather basal title: The Heart, Life, and Soul of Technology. According to G.K. Chesterton ( a famous English essayist, novelist, and critic), "All slang is metaphor and all metaphor is poetry." But my use of the metaphors Heart, Life and Soul in the title of this lecture (and of similar metaphors elsewhere in the lecture}, is largely a deliberate attempt to hum anise technology. Afterall, technology, like the sabbath, is made for man and not man for technology.